Unwanted detachment of the Solitaire device during mechanical thrombectomy in acute ischemic stroke. (27th January 2016) - Castaño, C; Dorado, L; Remollo, S; García-Bermejo, P; Gomis, M; Pérez de la Ossa, N; Millán, M; García-Sort, M R; Hidalgo, C; López-Cancio, E; Cubells, C; Dávalos, A
Abstract : Background: The use of retrievable stents for endovascular clot retrieval has dramatically improved successful revascularization and clinical outcome in selected patients with acute stroke. Objective: To describe the rate and clinical consequences of unwanted spontaneous detachment of these devices during mechanical thrombectomy. Methods: We studied 262 consecutive patients treated with the retrievable stent, Solitaire, for acute ischemic stroke between November 2008 and April 2015. Clinical, procedural, and outcome variables were compared between patients with and without unexpected detachment of this device. Detachment was classified as proximal to the stent proximal marker (type A) or distal to the marker (type B). Poor functional outcome was defined as modified Rankin scale score >2 at 90 days. Results: Unwanted detachment occurred in 6/262 (2.3%) cases, four of type A and two of type B. Stent recovery was possible in three patients, all of 'type A', but in none of 'type B'. The number of prior passes was higher in patients with undesired detachment (3 (2–5) vs 2 (1–3), p=0.007). Detachment was associated with higher rate of symptomatic intracranial hemorrhage (SICH) (33.3% vs 4.3%, p=0.001), poorer outcome (100% vs 54.8%, p=0.028), and higher mortality rate at 90 days (50% vs 17%, p=0.038). Conclusions: Unwanted detachment of a Solitaire is an uncommon complication during mechanical thrombectomy in patients with acute ischemic stroke and is associated with the clot retrieval attempts, SICH, poor outcome, and higher mortality.